Allelopathy of Ricinus communis and light spectrum variation decrease emergence and growth of Cyperus rotundus (Bioscience Journal, 2023)
Weeds negatively influence agricultural production. However, those losses depend on weed specie, its time of emergence, and period of interference on agricultural crops. Synthetic herbicides are commonly used to control these plants species; however, they may cause damage to the environment, human beings and animals health, and this problem justify the need to develop alternative bioherbicides. To evaluate the allelopathic potential of Ricinus communis (Castor bean) and light spectrum variation on the emergence and growth of Cyperus rotundus L., a trial was carried out in a protected environment with 15% of brightness reduction at the Center for Agricultural and Environmental Sciences at the Paraíba State University. Four aqueous extract concentrations of R. communis leaves were tested (0, 5, 10, and 15%) and four light spectrums variations (white, purple, blue, and red lights). Variables such as emergence, length, dry matter accumulation and growth rates of shoots and root of C. rotundus seedlings were assessed. Data were analyzed by normality test, analysis of variance, polynomial regression, and averages test. Soot and root emergence, length, and dry matter accumulation of C. rotundus seedlings were reduced due to the allelopathy caused by R. communis aqueous extract leaves (15% concentration) and under purple or red light spectrum radiation.